1998
DOI: 10.5271/sjweh.357
|View full text |Cite
|
Sign up to set email alerts
|

The accident process preceding overexertion back injuries in nursing personnel

Abstract: Engkvist I-L, Hagberg M, Wigaeus Hjelm E, Menckel E, Ekenvall L, PROSA study group. The accident process preceding overexertion back injuries in nursing personnel. Scand J Work Envi ron Health 1998;24(5):367-375. Objectives This prospective dynamic-population-based study investigated factors involved in the accident process preceding overexertion back injuries among nursing personnel. MethodsThe study covered all reported occupational overexertion back injuries due to accidents among of the approximately 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 21 publications
0
36
0
2
Order By: Relevance
“…The association between specific workplace risk factors (manual handling and transferring of patients) and the incidence of low-back injuries has been demonstrated in a large number of studies (6)(7)(8)(9). This is not surprising since biomechanical studies have demonstrated how low backloads during common patient handling tasks frequently exceed recommended safe limits for maximal acceptable compressive forces on the back (10,11).…”
mentioning
confidence: 93%
“…The association between specific workplace risk factors (manual handling and transferring of patients) and the incidence of low-back injuries has been demonstrated in a large number of studies (6)(7)(8)(9). This is not surprising since biomechanical studies have demonstrated how low backloads during common patient handling tasks frequently exceed recommended safe limits for maximal acceptable compressive forces on the back (10,11).…”
mentioning
confidence: 93%
“…28 In one study, nurses and nursing aides were found to be at particular risk of back injury during patient transfer, which require sudden movements in non-neutral postures. 29 Nurses, in our study, indicated that excess workload on direct patient care (82%) and nonnursing related activities (secretariat, etc.) (20.9%) were associated with their WRMD.…”
mentioning
confidence: 99%
“…Ergonomic assessment could prevent musculoskeletal injuries related to patient's transfer in the bed or to or from the bed [4,34]. Wearing cloves, not recapping used needles and proper disposal of sharp objects were the ways to prevent needle stick injuries [35].…”
Section: Discussionmentioning
confidence: 99%
“…Falls were the leading cause of occupational injury among health care workers, and facility support workers were at the highest risk of falling in hospitals [3]. The most frequent overexertion injury occurred during patient transfer to or from a bed [4]. Younger nurses in particular were prone to overexertion injuries [5].…”
Section: Introductionmentioning
confidence: 99%